2018
DOI: 10.26858/pdr.v2i1.13248
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Procrastination and Low Time Management on Student Self Efficacy (at MA Soebono Mantofani)

Abstract: Procrastination is the behavior that can not take advantage of time or procrastinate doing something. The purpose of this study was to determine the effect of procrastinating habits and low time management on student self efficacy in MA Soebono Mantofani. The method used is descriptive method with an associative approach. The sampling technique used was proportional random sampling using a sample of 61 respondents. The analysis tool uses validity test, reliability test, classic assumption test, regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Class management with the Independent curriculum with project-based learning and focus on students (Ersig & Williams, 2018;Saggaf, Salam, & Rifka, 2017;Sari, 2017;Yuangga & Sunarsi, 2018). The results of the study stated that 45% of teachers were very good at classroom management in the Merdeka curriculum, and 54% understood and mastered classroom management.…”
Section: Resultsmentioning
confidence: 99%
“…Class management with the Independent curriculum with project-based learning and focus on students (Ersig & Williams, 2018;Saggaf, Salam, & Rifka, 2017;Sari, 2017;Yuangga & Sunarsi, 2018). The results of the study stated that 45% of teachers were very good at classroom management in the Merdeka curriculum, and 54% understood and mastered classroom management.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, time management plays an important role in the academic achievement of students. Bad practices in time management are also cited as a significant cause of stress and poor academic performance [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…This distraction indicates a failure to manage time and is often linked to poorer academic outcomes for students (Park et al, 2018). Further, Yuangga and Sunarsi's (2018) study indicated that there was a simultaneous influence between procrastinating habits and low time management on student self-efficacy.…”
Section: Time Management and Procrastinationmentioning
confidence: 93%